2020
DOI: 10.3390/cancers12082254
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155-5p and MiR-203a-3p Are Prognostic Factors in Soft Tissue Sarcoma

Abstract: Soft tissue sarcoma (STS) is a heterogeneous group of rare malignancies with a five-year survival rate of approximately 50%. Reliable molecular markers for risk stratification and subsequent therapy management are still needed. Therefore, we analyzed the prognostic potential of miR-155-5p and miR-203a-3p expression in a cohort of 79 STS patients. MiR-155-5p and miR-203a-3p expression was measured from tumor total RNA by qPCR and correlated with the demographic, clinicopathological, and prognostic data of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Expression of miR-203 was enriched in keratinocytes and upregulated in inflammatory skin conditions, such as psoriatic lesions, where the expression of a series of cytokines was differentially regulated by miR-203 [ 14 ]. Aberrant expression of miR-203 was also reported in the tumorigenesis and cancer progressions of various tissue origins [ 27 30 ]. Contradictory results were presented in these studies with respect to the exact biological functions of miR-203 in regulating cell proliferation and cell inflammatory responses, at least partly explained by multiple downstream targets that had opposite impact on overlapping pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of miR-203 was enriched in keratinocytes and upregulated in inflammatory skin conditions, such as psoriatic lesions, where the expression of a series of cytokines was differentially regulated by miR-203 [ 14 ]. Aberrant expression of miR-203 was also reported in the tumorigenesis and cancer progressions of various tissue origins [ 27 30 ]. Contradictory results were presented in these studies with respect to the exact biological functions of miR-203 in regulating cell proliferation and cell inflammatory responses, at least partly explained by multiple downstream targets that had opposite impact on overlapping pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-203a gene is located on chromosome 14q32.33 (Griffiths-Jones et al 2006). It is aberrantly expressed in different diseases, such as osteosarcoma (Wu et al 2019), soft tissue sarcoma (Greither et al 2020), and pancreatic cancer (An and Zheng 2020), which suggests its expression to serve as a diagnostic marker. Interestingly, report shows that the miR-203a-3p is involved in the regulation of inflammation in diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Simpson et al reported that a comparison of gene expression between canine osteosarcomas and non-tumor tissue showed 1281 significantly differentially expressed genes (839 lower and 442 elevated gene expression), a subset of which were validated by qRT-PCR and immunohistochemistry [ 2 ]. Furthermore, Greither et al investigated the influence of miR-155-5p and miR-203a-3p expression on prognosis in patients with soft tissue sarcomas [ 3 ]. This study showed that increased expression of miR-155-5p was significantly associated with increased tumor stage, and that high miR-155-5p expression and low miR-203a-3p expression were significantly associated with poor survival in patients with soft tissue sarcomas.…”
mentioning
confidence: 99%